EFFECTS OF AGE AND SEASON ON THE BODY WEIGHT, SCROTAL CIRCUMFERENCE AND LIBIDO IN NILI-RAVI BUFFALO BULLS MAINTAINED AT THE SEMEN PRODUCTION UNIT, QADIRARAD - M. Younis, H.A. Samad, N. Ahmad and I. Ahmad (Pakistan Veterinary Journal, 2003)
This study was carried out to investigate effects of age and season on body weight, scrotal circumference and libido in 18 Nili-Ravi buffalo bulls kept at the Semen Production Unit, Qadirabad. Depending on age, these bulls were divided into three equal groups viz. young (3-4 years of age), adult (5-8 years of age) and old (12-15 years of age). Body weight and scrotal measurements were made at monthly intervals while libido of each bull was assessed weekly during the low (May to July) and the peak (September to November) breeding seasons. The results indicated that the body weight of adult and old bulls was higher (P<0.05) than young bulls. Similarly. The body weight was higher during peak than low breeding season. Scrotal circumference was higher in adult and old bulls than young bulls and during peak than low breeding season (P<0.05). The libido of the adult bulls was higher than young or old bulls, and during the peak than the low breeding season. It was concluded that body weight, scrotal circumference and libido of Nili-Ravi buffalo bulls were significantly affected by age of the bull and season of the year.